Women's Leadership in Music Modes, Legacies, Alliances - Nenic, Iva; Cimardi, Linda (Musik und Klangkultur, 2023)
Various modes of women's contemporary cultural, social and political leadership can be found in music. Informed by different histories and culturally bound social mores but also by a comparative perspective, the contributors of this volume ask what can be considered leadership in culture from women's point of view. They deconstruct the notion of leadership as corporative and career-related modes of success by showing how women's agency, power and negotiation in and through music can and should be considered as empowering, transformative and role-modeling. By interweaving several disciplinary perspectives - from ethnomusicology, musicology and cultural management to sociology and anthropology - this volume aims to substantially contribute to the study of women's leadership.